2016
DOI: 10.1002/pen.24437
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization, and thermomechanical properties of liquid crystalline epoxy resin containing ketone mesogen

Abstract: This study focuses on the synthesis of a novel liquid crystalline epoxy resin (LCER) based on ketone mesogenic group. The chemical structure, melting range, and liquid-crystalline phase transition behavior of the LCER were characterized using Fourier transform infrared spectroscopy, nuclear magnetic resonance spectroscopy, mass spectroscopy, differential scanning calorimetry (DSC), and polarized optical microscopy (POM). Two endothermal peaks and one exothermal peak appeared in the DSC curves. A birefringent l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…The K–LCE was synthesized following the method described in our previous work [ 9 ]. The synthetic route of K–LCE is shown in Scheme 1 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The K–LCE was synthesized following the method described in our previous work [ 9 ]. The synthetic route of K–LCE is shown in Scheme 1 .…”
Section: Methodsmentioning
confidence: 99%
“…However, common epoxy resins have poor thermal properties such as high CTE and low thermal conductivity (0.17–0.20 W/m·K), but these properties of epoxides can be improved by the rigid rod structures with liquid crystalline characteristics introduced [ 5 , 6 , 7 , 8 ]. We have reported that the liquid crystalline (LC) epoxy resin exhibited much lower CTE and a higher thermal conductivity (0.34 W/m·K) compared to those of a traditional epoxy resin (DGEBA) [ 9 ]. In general, the ICs are encapsulated by silica-filled epoxy composites, but the thermal conductivity of the composites is less than 1.0 W/m·K, which is far below the demand of ICs heat dissipation [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…This is attributed to the induced molecular orientation in the networked epoxy polymer chains. Frequently used mesogenic backbone structures include biphenyl, [4][5][6][7] terphenyl, 8 stilbene, [9][10][11][12][13][14][15][16][17][18][19][20] azomethine, [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] ester, [37][38][39][40][41][42][43][44][45][46][47][48][49] ketone, 50 and azo. 51,52 In an earlier study, we reported a remarkable improvement in both the thermal and mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Liquid crystalline (LC) epoxy resins are known to give both excellent mechanical and thermal properties due to the rigid mesogenic structure existing in the backbone moiety of networked polymer chains, such as biphenyl, 3 7 stilbene, 8 17 azomethine, 18 27 ester, 28 39 ketone, 40 and azo. 41,42 We have reported a remarkable improvement in fracture toughness and suggested the toughening mechanism of LC epoxy thermosets based on an analysis of the fracture process.…”
Section: Introductionmentioning
confidence: 99%